Congenital myasthenic syndromes: recent advances. Issue 5 (October 2016) - Beeson, David
Abstract : Purpose of review: Congenital myasthenic syndromes (CMS) are a group of heterogeneous inherited disorders caused by mutations in genes encoding proteins essential for the integrity of neuromuscular transmission. This review updates the reader on recent findings that have expanded the phenotypic spectrum and suggested improved treatment strategies. Recent findings: The use of next-generation sequencing is continuing to unearth new genes in which mutations can give rise to defective neuromuscular transmission. The defective transmission may be part of an overall more complex phenotype in which there may be muscle, central nervous system or other involvement. Notably, mutations in series of genes encoding presynaptic proteins are being identified. Further work on mutations found in the AGRN-MUSK acetylcholine receptor clustering pathway has helped characterize the role of LRP4 and broadened the phenotypic spectrum for AGRN mutations. Mutations in another extracellular matrix protein, collagen 13A1 and in GMPPB have also been found to cause a CMS. Finally, there are an increasing number of reports for the beneficial effects of treatment with β2-adrenergic receptor agonists. Summary: Recent studies of the CMS illustrate the increasing complexity of the genetics, pathophysiological mechanisms and the need to tailor therapy for the genetic disorders of the neuromuscular junction.